Kajian Pembatasan Angkutan Kargo Perusahaan Angkutan Udara Niaga Berjadwal dan Perusahaan Khusus Kargo - M. Herry Purnama (WARTA ARDHIA, 2010)
So far, Cargo transportation ran as well as there is no spesific problem, be cause commercial air transportation activity and special transportation company have spescial market segment clear regulation. If we see on Government no 40 tahn 1995 about air transportation that has been changed with government regulation no 3 th 2000 about air transportation in point 33 ayat 1 dan 3 that the tariff consist of passangers tariff and cargo tariff. cargo tariff is divided to be two tariff, there is cargo tariff International scheduled commercial transportation and domestic scheduled commercial transportation no scheduled transportation's price is based on agrement between service customer and transportation service provider. In Ministry of transportation’s regulation No. KM 25 Tahun 2008 about provider air transportation point 50 ayat 1, special domestic cargo air transpotation can be done schedully or not, meaning in this government regulation no prohibit limitation for commercial air transportation cargo.